An Analysis of Students' Difficulties on Online Learning in Speaking Skill at the Twelfth Grade Students of SMA N 3 Kota Jambi in Academic Year 2020/2021 - Ansiyatun Hidayah; Wennyta Wennyta; Khidayatul Munawwaroh (Universitas Batanghari Jambi, 2021)
This study aims to find out the difficulties on online learning in speaking skill. The researcher used a descriptive qualitative design by taking the sample used simple random sampling and then obtained XII Science 5 with the total number of 36 students, unfortunately three students did not fill the online questionnaires. Thus, there were 33 students as a sample. In collecting the data, the researcher used an online questionnaire. The result of this study showed the students’ difficulties on online learning in speaking skill were: Pronouncing problems 66.6%, students having difficulty interacting with others 63.6%, limited vocabulary 57.5%, lack of grammar 54.5%, poor internet connection 48,4%, students have not enough understanding to explore and express their ideas 33.3%, furthermore the students lack of fluency 21.2%.Keywords: Online learning, Online questionnaires, Speaking difficulties.